AVALIAÇÃO E COMPARAÇÃO DOS SISTEMAS COLOIDAIS DE LEITES UHT COMERCIALIZADOS NAS REGIÕES SUL E SUDESTE DO BRASIL - Gabriel de A. Farage; Ítalo T. Perrone; Rodrigo Stephani; Nathalia da S. Campos; Natália M. G. Alves (Química Nova)
EVALUATION AND COMPARISON OF COLOIDAL SYSTEMS OF UHT MILK MARKETED IN THE SOUTH AND SOUTHEAST REGIONS OF BRAZIL. Ultra high temperature (UHT) milk has great relevance in the Brazilian dairy market. Thermal processing, physical-chemical and compositional properties have relevant impact on the quality of milk processed via UHT. The emergence of new categories of this product makes the production scenario even more challenging. The aim of this study was to investigate UHT milk and the effect of food additives on it, from a colloidal perspective, in the main consumer regions. The colloidal systems of samples with or without addition of stabilizers and with or without addition of tricalcium phosphate were evaluated based on analyses of ionic calcium concentration, pH, sedimentation, HCT (heat coagulation time), ethanol stability, particle size (D90) and zeta potential. The results indicated a relevant colloidal stability for this type of matrix, in addition to an efficient industrial homogenization process. The samples that received stabilizers addition showed lower ionic calcium, higher HCT and greater ethanol stability. There was no significant difference in sediment mass and pH. The samples that received Ca3(PO4)2 addition showed higher sedimentation and lower stability to ethanol. There were no significant differences regarding ionic calcium, pH and HCT.